Perfil fermentativo de forrageiras nativas da caatinga - Santos, Maria do Socorro Almeida Arnaldo (2018)
The objective of this study was to characterize the nutritional potential of five native forage species of the caatinga through the in vitro gas production technique. The experimental design was in 5 x 2 factorial blocks, with five forage species: (Catingueira, Maniçoba, Marmeleiro, Quixabeira, Faveleira), with no addition of polyethylene glycol (PEG). The chemical-bromatological appearance was seen; disappearance, digestibility and cumulative in vitro gas production of organic matter, in addition to ruminal parameters. There is no significant interaction as species and treatment (with and without PEG). Based on the results of a faveleira, comparing them with other species, we can highlight the bromatological comparison of raw material, with superior and inferior fibers in neutral detergent (NDF), acid detergent fiber (FAD) and Lignin, resulting in a better DIVMO coefficient and higher gas accumulation. However, all species have increased the digestibility (above 60%), with the value of NNH3, FP, and microbial biomass, thus demonstrating a good fermentative efficiency. The inhibition of condensed tannins (increase of PEG) influenced in a significant way in a DIVMO, PGMO and biomass production, thus making a good efficiency of ruminal fermentation kinetics. good ruminal fermentation, and can be used for animal feed without semiarid.